2022
DOI: 10.1186/s12915-022-01312-4
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5-mediated JIP1 phosphorylation regulates axonal outgrowth through Notch1 inhibition

Abstract: Background Activated Cdk5 regulates a number of processes during nervous system formation, including neuronal differentiation, growth cone stabilization, and axonal growth. Cdk5 phosphorylates its downstream substrates located in axonal growth cones, where the highly expressed c-Jun N-terminal kinase (JNK)-interacting protein1 (JIP1) has been implicated as another important regulator of axonal growth. In addition, stringent control of the level of intracellular domain of Notch1 (Notch1-IC) play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In our previous study, we showed that Cdk5-mediated phosphorylation of JIP1 at Thr 205 promotes neuroaxonal outgrowth (Im et al 2022). Here, we investigated whether Cdk5-mediated phosphorylation of JIP1 at Thr 205 also plays a role in neuronal migration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we showed that Cdk5-mediated phosphorylation of JIP1 at Thr 205 promotes neuroaxonal outgrowth (Im et al 2022). Here, we investigated whether Cdk5-mediated phosphorylation of JIP1 at Thr 205 also plays a role in neuronal migration.…”
Section: Resultsmentioning
confidence: 99%
“…Although JIP1, one of them, has been demonstrated that its phosphorylation by Cdk5/p35 affects the speed of axon growth (Im et al 2022), the outcome of regulating neuronal migration on architecture of cerebral cortex remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Various molecular players that affect the speed of axon growth have been identified ( Fenlon, 2022 ). Although the JNK-interacting protein 1 (JIP1), one of them, has been demonstrated that its phosphorylation by cyclin-dependent kinase 5(Cdk5)/p35 affects the speed of axon growth ( Im et al, 2022 ), the outcome of regulating neuronal migration on architecture of cerebral cortex remains to be fully elucidated. The mammalian neocortex has a similar structure in rodents and primates, consisting of six layers of neurons that migrate from inner to outer regions during development.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin-dependent kinase 5 (Cdk5) is a proline-directed serine/threonine kinase, which is a unique component of the family of cyclin-dependent kinases (Dhavan and Tsai, 2001 ; Malumbres, 2014 ). Cdk5 plays a pivotal role in the nervous system, including cortex layer formation, synaptic growth and maturation, synaptic vesicular transport (Liu et al, 2022 ; Takahashi et al, 2022a ), stress-enhanced memory consolidation, dendritic spine formation, neuronal migration and differentiation, neurite outgrowth and length (Chen et al, 2017 ; Huang et al, 2017 ; Shinmyo et al, 2017 ; Lee et al, 2018 ; Nishino et al, 2019 ; Rao et al, 2020 ; Im et al, 2022 ), learning and long-term behavioral changes, axonal regeneration (Xu et al, 2017 ; Hwang and Namgung, 2021 ), brain microtubule network and actin cytoskeleton remodeling (Shah and Lahiri, 2017 ; Shah and Rossie, 2018 ), as well as normal cerebellar development and functions (Lee et al, 2019 ; Li et al, 2019 ; Kodani et al, 2020 ; Ouyang et al, 2020 ). Additionally, Cdk5 also plays a key role in gene expression, cell differentiation, angiogenesis, and aging (Arif, 2012 ).…”
Section: Introductionmentioning
confidence: 99%